Odpowiedzi

2010-02-11T20:35:45+01:00
-3x= 2x - 10 /-2x
-5x = - 10 /: 5
x= 2

2x - 2 = 7 - x
2x + x = 7+2
3x = 9 /:3
x = 3

10 = 4 - 2x
2x = 10 + 4
2x = 14
x = 7

-(2x-1)=4
- 2x + 1 = 4
- 2x = 3
x = - 2/3

2(x+1)=x
2x + 2 = x
x = -2

2t-(3t+1)=6
2t - 3t - 1 = 6
- t = 5
t = -5

-(4+x)=2(3-x)
- 4 -x = 6 - 2x
x = 10

3(y+6)-y=2(y+9)
3y + 18 - y = 2y + 18
3y - y - 2y = 18 - 18
0=0


(x-7)-2(3x+5)=3
x - 7 -6 - 10 = 3
x = 26
2010-02-11T20:38:45+01:00
A ) x = 10
b) x = 3
c) x = -3
d) x =- 2 1/2
e) 2x + 2 = x
x= -2
f) -6t - 2t = 6
-8t = 6
t = - 3/4
g) -4 - x = 6 - 2x
x = 10
h) 0 = 0
i) -5x = 20
x = -4 golega wyzej ma błedy z przenoszeniem i odejmowaniem ..!